Papua Under The State of Exception - Budi Hernawan (Antropologi Indonesia, 2020)
The paper argues that in post-Suharto's Indonesia, Papua remains under Carl Schmitt's state of exception in which law is suspended to allow executive power of the state to reign with little restrictions. The structure of domination has become much more complex as it no longer consists of dichotomy of the state authority and Papuan resistance movements. Rather, it colludes with the power of market, the monopoly of the powerful over natural resources as well as penetration of Wahhabism that undermines the existing cultural and social cohesion of the Papuans. The domination of the executive power of the state remains pervasive in the form of re-militarisation of Papua. The power of the market has placed Papua and Papuans under control of the economy elite who rules the game especially when it comes to land acquisition and extraction of natural resources. The politico-economy structure of domination has been exacerbated with the new phenomenon of Wahhabism that has undermined the cultural and social cohesion of the indigenous and non-indigenous Papuans. All these elements only affirm that the state of exception rules Papua as a frontier.